2019
DOI: 10.1080/1059924x.2019.1567420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety Management and Leadership Training Using Mobile Technologies among Logging Supervisors

Abstract: Background: Logging is recognized as one of the most dangerous industries in the United States (US), ranking among those with the highest occupational injury and fatality rates. Although logging operations in the Southeastern US have lower rates of injuries and fatalities compared to other regions of the US, due in part to the use of large machinery to fell timber as opposed to chainsaw felling, safety hazards continue to persist. The hazards present in the logging cut sites in which loggers operate may resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…Berumen-Flucker et al 57 reported an increase in the rate of adoption of safety and health management practices and the performance of safety audits by supervisors. Positive changes in terms of quality and quantity of supervisors' toolbox talks post training were discovered, 60,61 which is important because this safety communication method is commonly used in the construction industry.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Berumen-Flucker et al 57 reported an increase in the rate of adoption of safety and health management practices and the performance of safety audits by supervisors. Positive changes in terms of quality and quantity of supervisors' toolbox talks post training were discovered, 60,61 which is important because this safety communication method is commonly used in the construction industry.…”
Section: Resultsmentioning
confidence: 99%
“…Supervisors' reaction to training (level 1) was assessed in four studies. 57,58,60,62 Two studies assessed supervisory safety attitudes (level 2a). 58,60 Majority of the studies assessed supervisory acquisition of knowledge and skills (level 2b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations